2005
DOI: 10.1111/j.1523-1755.2005.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathologic characteristics of dilated cardiomyopathy in hemodialysis patients

Abstract: The pathologic characteristics of the heart in dialysis patients with DCM are interstitial fibrosis and severe myocyte hypertrophy with occasional disarray. The extent of LV fibrosis is a strong predictor of cardiac death. Careful follow-up and treatment are necessary for dialysis patients with a high percent area of LV fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 22 publications
9
114
0
2
Order By: Relevance
“…It is feasible that abnormal GLS is the precursor of overt uremic cardiomyopathy in dialysis patients. The mechanisms of abnormal GLS in ESRD are not fully clear, but may reflect interstitial fibrosis with myocyte hypertrophy (31). Furthermore, less negative GLS may be also associated with microvascular ischemia caused by the reduction in the density of myocardial capillaries, myocardial fibrosis, or hemodialysis-related myocardial stunning (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…It is feasible that abnormal GLS is the precursor of overt uremic cardiomyopathy in dialysis patients. The mechanisms of abnormal GLS in ESRD are not fully clear, but may reflect interstitial fibrosis with myocyte hypertrophy (31). Furthermore, less negative GLS may be also associated with microvascular ischemia caused by the reduction in the density of myocardial capillaries, myocardial fibrosis, or hemodialysis-related myocardial stunning (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Over time this stress of myocardial cells may result in partial apoptosis and subsequently in a progressive fibrosis that may develop in small areas of ischemia. Such extensive fibrosis is a further bad prognostic criteria in hemodialysis patients (49).…”
Section: Discussionmentioning
confidence: 99%
“…There are many potential reasons for the problem of sudden death: Abnormalities in the coronary microcirculation; impaired coronary reserve; reduced aortic compliance; increased activity of the sympathetic nervous system; the increased plasma concentration of angiotensin II; and sudden changes in the concentrations of potassium, calcium, and magnesium (which occur normally during dialysis) all can contribute to this problem. Another recent contributor to the problem of sudden death in this patient population may be related to the degree of fibrosis in the hearts of individuals on dialysis (22). In a recent study by Aoki et al (22), myocardial biopsies revealed abnormal cardiac myocyte anatomy and an interposition of dense fibrosis in the hearts of individuals who were on dialysis.…”
Section: Overview Of the Problem Of Cardiovascular Disease In Patientmentioning
confidence: 99%